2009
DOI: 10.1161/circresaha.108.189779
|View full text |Cite|
|
Sign up to set email alerts
|

Angiotensin II–Mediated Adaptive and Maladaptive Remodeling of Cardiomyocyte Excitation–Contraction Coupling

Abstract: Abstract-Cardiac hypertrophy is associated with alterations in cardiomyocyte excitation-contraction coupling (ECC) and Ca 2ϩ handling. Chronic elevation of plasma angiotensin II (Ang II) is a major determinant in the pathogenesis of cardiac hypertrophy and congestive heart failure. However, the molecular mechanisms by which the direct actions of Ang II on cardiomyocytes contribute to ECC remodeling are not precisely known. This question was addressed using cardiac myocytes isolated from transgenic (TG1306/1R [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…The fact that LKRs do not display increased pressor values suggests that the observed cardiac hypertrophy is not linked to alterations in afterload. This is in accord with the fact that a chronic increase in plasma AII levels causes a significant change in cardiomyocyte excitation-contraction coupling and, therefore, contractility, giving rise to cardiac hypertrophy independently of hemodynamic overloading and arterial hypertension (Gusev et al, 2009). Therefore, it is tempting to speculate that in the LKR strain, chronic RAS activation could give rise to a macroscopically visible increase in heart size.…”
Section: Discussionsupporting
confidence: 53%
“…The fact that LKRs do not display increased pressor values suggests that the observed cardiac hypertrophy is not linked to alterations in afterload. This is in accord with the fact that a chronic increase in plasma AII levels causes a significant change in cardiomyocyte excitation-contraction coupling and, therefore, contractility, giving rise to cardiac hypertrophy independently of hemodynamic overloading and arterial hypertension (Gusev et al, 2009). Therefore, it is tempting to speculate that in the LKR strain, chronic RAS activation could give rise to a macroscopically visible increase in heart size.…”
Section: Discussionsupporting
confidence: 53%
“…Eventually this results in diastolic dysfunction, followed by contractile dysfunction, leading to an increased risk of arrhythmia [44,69]. ECC, where electrical excitation of cardiomyocytes drives contraction of the heart, is also affected by AngII-remodelling processes, with alterations in the calcium sensitivity of calcium-handling proteins and changes in ion current expression in cardiomyocytes leading to altered intracellular calcium concentrations, which in turn may reduce cardiac contractility [70].…”
Section: Functional and Electrical Remodelling In The Heartmentioning
confidence: 99%
“…It is a peripheral vasodilator, powerfully inotrope and may affect central fluid homeostasis [6,7]. Animal and human studies suggested that it might play a role in the pathogenesis of heart failure by modulating the harmful effects of Ang II [8,9]. The diastolic reactivity of apelin in ex vivo vascular rings of SHR (spontanously hypertensive rat) is reduced and the effect is mediated by NO pathway and the ERK1/2 pathway [10].…”
Section: Introductionmentioning
confidence: 99%